Penggunaan Metode Goal Programming Untuk Optimasi Perancangan Proses Produksi Produk Wingko Babat - Novitasari, Novitasari; Talitha, Tita; Susanto, Dewi Agustini (Universitas Dian Nuswantoro, 2017)
One form of actual problems in the manufacturing industry is how to maximize the value of profit with various constraints or constraints. The problem is not only experienced by big industry but also small industry like in UD. Wingko trip Mr. Moel who is trying to maximize the value of profit by estimating the amount of wingko trips that must be produced because there is a problem of the difference in the amount of production with one of the limits associated with the production capacity. The resulting production difference causes the amount of wingko trip or excess production in certain month. The method of Goal Programming is the one method of optimization with more than one objective that are interconnected with each other or conflicting to solve the problem. This research uses the Goal Programming method to optimize the production amount and maximize the profit of the product, and to forecast the number of forward demand by using the number of the past request to know how many products must be produced. Goal Programming Formulations use forecasting as decision variables for optimization of results in compliance with criteria and constraints. The results show the optimal amount of production in January - December 2017 are 29860 bag wingko original, 24000 bag wingko chocolate chocolate, 26004 bag wingko tripe jackfruit and 18084 bag wingko tripe durian with total profit in 2017 is Rp. 429.736.600.Â